Effects of Biosolids at Varying Rates on Earthworms (Eisenia fetida) and Springtails (Folsomia candida) - N. Artuso; T. F. Kennedy; J. Connery; J. Grant; O. Schmidt (Applied and Environmental Soil Science)
Land spreading is a major option internationally for the disposal/use of treated sewage sludge (biosolids), but effects of this practice on soil organisms are largely unknown. This study investigated the effects of biosolids on two soil invertebrate species, earthworms (Eisenia fetida) and Collembola (Folsomia candida), in laboratory tests. Five biosolids from different sewage works were assessed at rates equivalent to 0, 2, 5, 10, and 20 t ha−1. Biosolids applied at 2 and 5 t ha−1 did not cause mortality of adult earthworms but did at 10 and 20 t ha−1. At 5, 10 and 20 t ha−1, all biosolids had significantly fewer juvenile worms relative to controls. Increasing the rates from 2 to 10 t ha−1 did not impact on the number of adult Collembola, but at 20 t ha−1 there were significantly fewer adults. There were significantly fewer juvenile Collembola recorded for biosolids applied at the 2 t ha−1 when compared with controls, and also when biosolids were applied at 5, 10, and 20 t ha−1 relative to 2 t ha−1. Some significant difference between biosolids were observed, but generally, negative effects were not related to heavy metal concentrations in biosolids. It is recommended that possible detrimental mechanisms (e.g., ammonia production, lack of oxygen) be investigated in future work. It is concluded that biosolids, applied at legal, low rates (about 2 t ha−1) are unlikely to be detrimental to earthworms or adult Collembola but can be detrimental to Collembola reproduction.